Pomoc państwa dla górnictwa węgla kamiennego w świetle przepisów unijnych - Gawlik, Lidia; Pepłowska, Monika (Polityka i Społeczeństwo, 2020)
The authors have analyzed the documents containing legal regulations directly related to the coal mining sector. They referred to a number of both national laws and laws set by the authorities of the European Union (EU). The authors pay attention to the special role of coal in resource policy of Poland. They show the conditions under which state aid was granted to the coal mining industry based on the specific directives, laws and regulations in the previous years. Moreover assumptions of national aid programs are described, and the possible restructuring actions that might be accomplished with the help of this financial assistance are demonstrated. Also the authors hold a discussion on the legitimacy of the use of publicly-legislated aid in the coal mining industry.